Parsing neurobiological heterogeneity of the clinical high-risk state for psychosis: A pseudo-continuous arterial spin labelling study - Oliver, Dominic; Davies, Cathy; Zelaya, Fernando; Selvaggi, Pierluigi; De Micheli, Andrea; Catalan, Ana; Baldwin, Helen; Arribas, Maite; Modinos, Gemma; Crossley, Nicolas A.; Allen, Paul; Egerton, Alice; et al. (Frontiers in Psychiatry, 2023)
The impact of the clinical high-risk for psychosis (CHR-P) construct is dependent on accurately predicting outcomes. Individuals with brief limited intermittent psychotic symptoms (BLIPS) have higher risk of developing a first episode of psychosis (FEP) compared to individuals with attenuated psychotic symptoms (APS). Supplementing subgroup stratification with information from candidate biomarkers based on neurobiological parameters, such as resting-state, regional cerebral blood flow (rCBF), may help refine risk estimates. Based on previous evidence, we hypothesised that individuals with BLIPS would exhibit increased rCBF compared to APS in key regions linked to dopaminergic pathways. Data from four studies were combined using ComBat (to account for between-study differences) to analyse rCBF in 150 age- and sex-matched subjects (n=30 healthy controls [HCs], n=80 APS, n=20 BLIPS and n=20 FEP). Global grey matter (GM) rCBF was examined in addition to region-of-interest (ROI) analyses in bilateral/left/right frontal cortex, hippocampus and striatum. Group differences were assessed using general linear models: i) alone; ii) with global GM rCBF as a covariate; iii) with global GM rCBF and smoking status as covariates. Significance was set at p<0.05. Whole-brain voxel-wise analyses and Bayesian ROI analyses were also conducted. No significant group differences were found in global (F(3,143)=1,41, p=0.24), bilateral frontal cortex (F(3,143)=1.01, p=0.39), hippocampus (F(3,143)=0.63, p=0.60) or striatum (F(3,143)=0.52, p=0.57) rCBF. Similar null findings were observed in lateralised ROIs (p>0.05). All results were robust to addition of covariates (p>0.05). No significant clusters were identified in whole-brain voxel-wise analyses (p>0.05FWE). Weak-to-moderate evidence was found for an absence of rCBF differences between APS and BLIPS in Bayesian ROI analyses. On this evidence, APS and BLIPS are unlikely to be neurobiologically distinct. Due to this and the weak-to-moderate evidence for the null hypothesis, future research should investigate larger samples of APS and BLIPS through collaboration across large-scale international consortia.